Modelagem do tamanho de grão resultante da recristalização dinâmica durante laminação a quente de um aço inoxidável 316L - Machado, Marcelo Watanabe (Universidade Federal de São Carlos, 2023)
Austenitic stainless steels are known for having a wide service temperature range, formability, ductility, weldability, and good corrosion resistance. In particular, the AISI 316L stainless steel (austenitic) has molybdenum and low carbon content, which adds to a greater corrosion resistance when compared to a 304, the most commercially used stainless steel. However, before reaching the properties which give the referred qualifications to the material, it is of fundamental importance that it goes through several processing stages (e.g. heat treatment, mechanical forming, etc.) that submit it to an adequate thermomechanical history leading to an adequate microstructure that promotes the desired final properties together with compositional aspects. In this scenario, it is essential to design processes to fulfill such functionality by having a set of parameters as close as possible to ideal. Thus, methods as finite element simulations are of great importance to optimize the processing parameters. In this way, the current work intends to analyze the representativeness of a proposed model in the literature to describe the dynamic recrystallization (DRX) of a AISI 316LN stainless steel when used for a AISI 316L hot rolled stainless steel. The comparison was, thus, between the average grain size value obtained by thermomechanical processing and by finite element simulation. For this purpose, an experimental hot rolling was performed in three different temperatures, followed by metallography with electrolytic etching aiming for grain revelation enabling average grain size measurement using optical microscopy. Herewith, it was possible to observe not only the above-mentioned parameter, but also signs of the presence of other phases like ε-martensite and δ-ferrite. The presence of δ-Fe was confirmed by its X-ray diffraction peaks in a no heat-treated sample. Additionally, it was possible to notice discontinuous dynamic recrystallization (DRX mechanism) evidence and compatibility between simulated average grain size values range and values acquired experimentally for two out of three tested temperatures (1000°C and 1100°C). A less than 1 μm difference can be related to experimental errors, not taking into account some factors during model’s conception and variations originated from the use of constants obtained for AISI 316LN stainless steel for the study of phenomena in a AISI 316L stainless steel.
Modeling the grain size resulting from dynamic recrystallization during hot rolling of a 316L stainless steel
Keywords: Laminação a quente; AISI 316L; Aço Inoxidável Austenítico; Simulação por elementos finitos; QForm; Recristalização dinâmica; Hot Rolling; Austenitic Stainless Steel; Finite element simulation; Dynamic recrystallization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA